Facial Nerve Paralysis or Facial Palsy - Choombuathong, Anchalee (Journal of Health Science of Thailand, 2017)
Bell’s palsy is a form of facial paralysis resulting from a dysfunction of facial nerve that results in the inability to control facial muscles on the affected side. Symptoms of Bell’s palsy range in severity from mild weakness to total paralysis on ipsilateral face of the lesion. Other symptoms may include drooping of the eyelid and corner of the mouth, impairment of taste, and excessive tearing in one eye. The definite etiology of the disorder has not been well understood. However, reactivation of the herpes simplex virus infection, latented in the geniculate ganglion of the facial nerve, is a widely accepted pathophysiological mechanism. Some studies have shown that corticosteroid such as prednisone is used to reduce inflammation and swelling. Other drugs such as antivirus is used to fight viral herpes infections. However, the current practice of treating Bell’s palsy with antivirus treatment plus corticosteroid may lead to slightly higher recovery rates compared to treating with corticosteroid alone. The prognosis of Bell’s palsy is related to the severity of the lesion. A simple rule is that clinically incomplete lesions tend to recover. Typically, the symptoms will recover within 21 days after initial onset. Exceptions are made with some clinical factors such as severity of facial weakness, delayed oral prednisolone treatment. Though up to 85 percent of the cases have favorable outcome and recover completely within 3 to 6 months after treatment.